2010
DOI: 10.1038/ng.651
|View full text |Cite
|
Sign up to set email alerts
|

The ratio of human X chromosome to autosome diversity is positively correlated with genetic distance from genes

Abstract: The ratio of X-linked to autosomal diversity was estimated from an analysis of six human genome sequences and found to deviate from the expected value of 0.75. However, the direction of this deviation depends on whether a particular sequence is close to or far from the nearest gene. This pattern may be explained by stronger locally acting selection on X-linked genes compared with autosomal genes, combined with larger effective population sizes for females than for males.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
126
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(147 citation statements)
references
References 15 publications
20
126
1
Order By: Relevance
“…S2) are unlikely to explain this pattern, and rather we argue that the reduced variation on the X chromosome is driven by a combination of more efficient selection against detrimental variants and selection for advantageous recessive mutations. Recent studies in humans have also reported a reduced X/A ratio near genes and interpreted this as HillRobertson effects (10,12,27). Purifying selection is, if anything, marginally stronger on the X chromosome than on autosomes in chimpanzees (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…S2) are unlikely to explain this pattern, and rather we argue that the reduced variation on the X chromosome is driven by a combination of more efficient selection against detrimental variants and selection for advantageous recessive mutations. Recent studies in humans have also reported a reduced X/A ratio near genes and interpreted this as HillRobertson effects (10,12,27). Purifying selection is, if anything, marginally stronger on the X chromosome than on autosomes in chimpanzees (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…S1). In humans, X to autosome diversity ratios range from 0.57 (Europeans) to 0.7 (Africans) near genes and between 0.75 (Europeans) and 0.87 (Africans) far away from genes (3,(10)(11)(12). We used the human reference genome to orient SNPs (Methods) and obtain the unfolded site frequency spectrum (SFS) at both synonymous and nonsynonymous sites (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Part of the variation in these ratios is associated with differences in recombination and distance from coding loci (and effects of selection). Hammer et al (2010) found that the adjusted ratio increased from 0.89 to 1.48 as the recombination distance from functional loci increased. Further, Vicoso and Charlesworth (2009) reported an adjusted ratio for nucleotide diversity in Drosophila melanogaster for non-coding regions of X chromosomes: autosomes of 1.57, but the adjusted ratio was 0.97 for regions with similar effective recombination rates on X and autosomes.…”
Section: And Z Chromosomesmentioning
confidence: 97%
“…Individual identifiers for each of these samples are described in Wall et al (35). Our updated resequence dataset consists of 61 loci in autosomal intergenic regions (36), each z20 kb of primarily single-copy noncoding (i.e., putatively nonfunctional) DNA in regions of medium or high recombination (ρ $ 0.9 cM/ Mb) at least 100 kb away from the nearest gene (37). We used a locus trio design, sequencing three fragments of z2 kb spaced evenly across the region (35).…”
Section: Methodsmentioning
confidence: 99%